3. Islam w Kirgistanie .......... 207 - Saprynskaja, Daria; Sokołowskij, Iwan (Kirgistan – oblicza transformacji, 2020)
ISLAM IN MODERN KYRGYZSTANIslam in modern Kyrgyzstan is experiencing a revival, associated with a dynamic increase in the number of people declaring themselves as Muslims, the increase in the number of Islamic temples and the expansion of the appropriate organizational structure. It is true that the constitution of the republic defines Kyrgyzstan as a secular state, nevertheless, Islamic religion is increasingly becoming an integral component of social life, while being at the same time an element of ethnic and national identity. The article shows the panorama of Islamic religious life in the republic and the religious organizations operating there: both those legal and those recognized as extremist.